Narrative, Ethics, and the Development of Identity - Freeman, Mark (Narrative Works)

(untitled) (Centre for Interdisciplinary Research on Narrative, St. Thomas University, 2014)
The terms “narrative” and “development” would appear to be difficult to relate to one another. While “narrative” frequently connotes movement backward in time and would thus seem to be a retrospective concept, “development” connotes movement forward in time and would thus seem to be a prospective concept. In this article, I seek to rethink both of these terms in such a way as to render them more compatible. In doing so, I focus on the idea of narrative identity, which, I suggest, is not only about the self but about the other-than-self, especially those goods that draw the process forward.